Fungal degradation of recalcitrant nonphenolic lignin structures without lignin peroxidase. - Srebotnik, E (1994)
Lignin peroxidases (LiPs) are likely catalysts of ligninolysis in many white-rot fungi, because they have the unusual ability to depolymerize the major, recalcitrant, non-phenolic structures of lignin. Some white-rot fungi have been reported to lack LiP when grown on defined medium, but it is not clear whether they exhibit full ligninolytic competence under these conditions. To address this problem, we compared the abilities of a known LiP producer, Phanerochaete chrysosporium, with those of a reported nonproducer, Ceriporiopsis subvermispora, to degrade a synthetic lignin with normal phenolic content, a lignin with all phenolic units blocked, and a dimer, 1-(4-ethoxy-3-methoxyphenyl)-2-(2-methoxyphenoxy)propane-1,3-diol, that represents the major nonphenolic structure in lignin. P. chrysosporium mineralized all three models rapidly in defined medium, but C. subvermispora showed appreciable activity only toward the more labile phenolic compound under these conditions. However, in wood, its natural environment, C. subvermispora mineralized all of the models as rapidly as P. chrysosporium did. Defined media therefore fail to elicit a key component of the ligninolytic system in C. subvermispora. A double-labeling experiment with the dimeric model showed that a LiP-dependent pathway was responsible for at least half of dimer mineralization in wood by P. chrysosporium but was responsible for no more than 6-7% of mineralization by C. subvermispora in wood. Therefore, C. subvermispora has mechanisms for degradation of nonphenolic lignin that are as efficient as those in P. chrysosporium but that do not depend on LiP.